Fe(II)-loaded goat manure biochar efficiently activated peroxymonosulfate for tetracycline degradation in groundwater - Fan, Lianjie; Xie, Qinglin; Li, Yanhong; Zou, Shengzhang; Lu, Haiping; Li, Su Ling; Li, Xiaoxiao (Frontiers in Environmental Science, 2024)
Poultry manure is one of the important sources of antibiotic pollution in agricultural soil and groundwater. Recently, the excessive discharge of goat manure has resulted in groundwater environmental challenges and negative impacts. It is of practical significance that such wastes can be converted into functional materials to promote the resource utilization of waste and reduce the risk of antibiotic contamination. In this study, Fe (Ⅱ)-loaded goat manure biochar (Fe-GMC) was prepared by pyrolyzing goat manure and iron salts and used to activate peroxymonosulfate (PMS) for tetracycline (TC) degradation in groundwater. The as-prepared Fe-GMC exhibited good catalytic performance for PMS activation due to its porous surface and rich oxygen-containing groups. Under the conditions of catalyst dosage of 0.2 g/L, PMS dosage of 1.0 mM, and pH of 3.0, TC was removed 81.3% within 60 min. In addition, the TC degradation efficiency was inhibited to different extents by inorganic anions (HCO3−>Cl−>NO3−) in water. Furthermore, the quenching experiments, electron paramagnetic resonance (EPR) experiments, and X-ray photoelectron spectroscopy (XPS) spectra analysis indicated that the generation of hydroxyl radicals (•OH) was responsible for TC degradation. Particularly, Fe-GMC produces a strong oxidizing agent. This study provides an efficient and environmentally friendly tetracycline degradation catalyst, which offers a new theoretical basis for water environmental remediation.